Use of an observer tool to enhance learning of anaesthesia resident’s non-technical skills during high-fidelity simulation: a randomised controlled trial - Caroline Havard; Viridiana Jouffroy; Agnès Le Gouez; Marie Bruyère; Samy Figueiredo; Philippe Roulleau; Dan Benhamou; Aurore Margat; Antonia Blanié (BMC Medical Education)
Abstract Background The use of an observer tool (OT) has been shown to improve learning of technical skills through observation in simulation. The objective was to assess the impact of a non-technical OT on anaesthesia residents’ learning of non-technical skills (NTS) during simulation. Methods After consent, residents were randomised into 2 groups: OT+ (with an OT based on NTS to be systematically completed during observation of others) and OT- (without OT). Both groups observed a high-fidelity simulation of crisis management (with or without OT), then were asked to perform actively another simulation. The primary outcome was NTS performance, assessed by an evaluator using the Anaesthesia Non-Technical Skills score (ANTS score out of 16) on video recording. Secondary outcomes were results of score items, satisfaction, team performance, and professional impact. Results No significant difference was found between OT + group (n = 33) and OT- group (n = 30) for the ANTS score (OT + 12 [9.5–12.5], OT- 10.5 [8.75–12]/16 (p = 0.13)). Among sub-items of the ANTS score, decision-making was significantly better in the OT + group (3 [2–3] versus 2 [2–3], p = 0.01). Satisfaction, team performance and perception of professional impact were not significantly different between groups. Conclusions This study showed no significant difference in learning of observational anaesthesia resident’s NTS whether or not they were provided a non-technical OT during crisis management simulation. Decision-making was better with an OT. Further work is necessary to define the place of OT in observer-based learning.